SOCIO-SEMANTICS ANALYSIS OF SLANG WORDS USED IN WE OWN THE NIGHT MOVIE MANUSCRIPT - YULIYANTO, YULIYANTO (2011)
This research aims at describing the variations of language form and the meaning of slang words used in We Own the Night movie manuscript. The type of this research is descriptive qualitative. The technique of collecting data is documentation method, and the steps are watching the original movies, noting, retyping, coding, and analyzing the data of slang words. To achieve the first objective of the research, the writer refers to Dineen's theory of linguistics form to identify the variation of language form in slang words. While the second objective is uses Larson's theory of meaning and Poedjosoedarmo's theory of change of meaning to describe the lexical and contextual meaning. The result of the study shows that the language forms of slang words We Own the Night movie manuscript is words. The words can be divided into the structural word and the functional word. The structural words are 13, 79% verb, 44, 62% noun, 20,69% adjective and 3, 45% adverb, while the functional word are 10, 34% auxiliary and 3,45% preposition. The meaning of slang words are divided into lexical and contextual meaning; the lexical meaning of slang words are 37, 93% and the contextual of slang words are 100%. The change of meaning are 17, 24% the new meaning of the word could be broader than its real meaning, 13,79% the real meaning of the word could be broader than the new meaning represented by the same words, 6, 89% the real meaning and the new meaning of the word are identical, and 62, 06% the new meaning does not have the real meaning.